Handbook for Clinical Memory Assessment of Older Adults. 1986
DOI: 10.1037/10057-009
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of presenting symptoms.

Abstract: The major mental disorders in the aged are associated with a few notable pathologic syndromes. Excellent, brief, standardized instruments have been available for several years for the assessment of all the major pathologic syndromes with the exception of cognitive impairment. I n recent years, clinical instruments for the assessment of cognitive decline in Alzheimer's disease, and in other geriatric pathologies with cognitive concomitants, have been deueloped.The rationale, validation, and utilitarian aspects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

1989
1989
1996
1996

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…This disability results in the clinical observation of disorientation to place and time (Daniel, 1988;Daniel & Crovitz, 1982;Kahn, 1986;Reisberg et al, 1986). The amnesic person often cannot recall the name of the current setting, such as the hospital, or recent events, such as meals or visits from the family.…”
mentioning
confidence: 97%
“…This disability results in the clinical observation of disorientation to place and time (Daniel, 1988;Daniel & Crovitz, 1982;Kahn, 1986;Reisberg et al, 1986). The amnesic person often cannot recall the name of the current setting, such as the hospital, or recent events, such as meals or visits from the family.…”
mentioning
confidence: 97%
“…According to Wells, it is the discrepancies in the appearance of these difficulties which could prove most diagnostic. In a prospective study, Reisberg et al (1986) found that, by and large, AD patients might be expected to choose the proper clothing to wear (eg pyjamas at night) before losing the ability to put it on properly). Not infrequently, those with depressive dementia will show inconsistencies such as incontinence while still being able to dial the telephone.…”
Section: Personal and Social Skillsmentioning
confidence: 99%
“…Only depressives who scored in the 'normal range' of the Mini-Mental State Examination (MMSE) were selected however while none of the A D patients were in mild stages. Other evidence instead shows that, in many patients with early AD, complaints of specific memory failures are the presenting grievance and are congruent with their spouse's evaluation of their predicament (Reisberg et al, 1986). Conversely, elderly depressives tend to exhibit a high degree of complaining overall.…”
Section: Complaintsmentioning
confidence: 99%
See 1 more Smart Citation
“…Commonality among the indexes is near perfect (r = 97) (Reisberg, Ferris, & Borenstein, 1987). The rating scale characterizes the degree of impairment, from normal to very severe, on five global axes (concentration, short term/long term memory, orientation, and self-care).…”
Section: B Rief Cognitive Rating Scale (Bcrs)mentioning
confidence: 99%